Econometric Analysis of the Relationship Between Crop Yields Under Agricultural Risk Diversification - Baymirzaev Dilmurod Nematovich (Academia Open, 2025)
General Background: Agricultural diversification is a vital strategy for reducing systemic risks and stabilizing farm income under climate variability. Specific Background: In Uzbekistan, particularly in the Namangan region, limited empirical evidence exists on how wheat and cotton yields interact within the framework of risk diversification. Knowledge Gap: Despite global studies on crop diversification, the causal and econometric relationships between major crops under local environmental conditions remain underexplored. Aims: This study examines the temporal and econometric interdependence between wheat and cotton yields from 1990 to 2024 using correlation analysis, Granger causality tests, and Vector Autoregression (VAR) modeling. Results: Findings reveal that while most districts exhibit weak or negative correlations conducive to diversification, the Chust district shows a strong positive yield relationship due to similar agronomic conditions. Granger causality indicates that in Kosonsoy and Norin, wheat yield significantly influences cotton yield, whereas in Turaqo‘rg‘on the reverse holds true. Novelty: The study introduces a district-level econometric assessment of inter-crop dynamics, highlighting asymmetric causal patterns shaped by soil and water resource variations. Implications: Results suggest that optimizing crop rotation and water distribution can mitigate covariate risks and stabilize farmers’ income, offering evidence-based guidance for regional agricultural policy in Uzbekistan.Highlight : The study examines the econometric relationship between wheat and cotton yields under agricultural risk diversification in Namangan region. Results show varied correlations and causal directions, influenced by soil and water resource conditions. Findings support policies to enhance crop rotation, resource management, and income stability for farmers. Keywords : Agricultural Risks, Diversification, Wheat, Cotton, Yield